Molecular Basis of Chemotherapy and Radiotherapy Treatments Resistance in Cancer Management - Abu, Michael Sunday; Yakubu, Ojochenemi Ejeh; Timothy, Mgbede; Umaru, Isaac John (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Cancer is a leading cause of death worldwide. Surgery is the primary treatment approach for cancer, but the survival rate is very low due to the rapid progression of the disease and presence of local and distant metastasis at diagnosis. Adjuvant chemotherapy and radiotherapy are important components of the multidisciplinary approaches for cancer treatment. However, resistance to radiotherapy and chemotherapy may result in treatment failure or even cancer recurrence. Radioresistance in cancer is often caused by the repair response to radiation-induced DNA damage, cell cycle dysregulation, cancer stem cells (CSCs) resilience, and epithelial-mesenchymal transition (EMT). Understanding the molecular alterations that lead to radioresistance may provide new diagnostic markers and therapeutic targets to improve radiotherapy efficacy. Patients who develop resistance to chemotherapy drugs cannot benefit from the cytotoxicity induced by the prescribed drug and will likely have a poor outcome with these treatments. Chemotherapy often shows a low response rate due to various drug resistance mechanisms. This review focuses on the molecular mechanisms of radioresistance and chemoresistance in cancer and discusses recent developments in therapeutic strategies targeting chemoradiotherapy resistance to improve treatment outcomes.